Bangladesh : Unravelling the 'Good Health at Low Cost' Story - Ahmed, Shakil; Begum, Tahmina; Cotlear, Daniel (World Bank, Washington, DC, 2019)
This case study describes Bangladesh’s success story using the standardized approach used by the Universal Health Coverage Studies Series (UNICO Studies Series) to provide a balanced account of the key pillars that lay behind the success of pluralism in the health system of Bangladesh. The aim is to recognize the contributions of the different actors (including the Government and the informal sector, which in the past have not been sufficiently recognized) and the strengths and weaknesses of these pillars as the needs and opportunities evolve due to emerging health issues. This lack of knowledge is an impediment to policy formulation and implementation aimed at maintaining the success of Bangladesh in the health sector. The case study suggests that there were four pillars to the successful pluralism that characterized Bangladesh: (a) effective prioritization of public financing on highly cost-effective interventions, (b) effective alignment of government and DP financing based on the mechanism of the SWAp, (c) extensive use of female CHWs and innovative NGOs, and (d) a large informal private sector that functions as a retailer of an unusually large and competitive domestic pharmaceutical industry. It should be acknowledged that determinants such as significant poverty reduction, education of girls, female labor force participation, and water and sanitation interventions outside the health sector also played a significant role in achieving better health outcomes.